Taṭwīr Kitāb “Ayo Belajar Bahasa Arab Untuk MI Kelas IV” Bi Barnāmij al-`Arūḍ at-Taqdīmiyyah Bi SDIT Quantum School - Lilis Putri Sari; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
The development of a method is research conducted to produce a specific product. Textbooks the prominent sources to attract student’s attention. The content of the grammar in the textbook makes students bored and lack enthusiasm for Arabic lessons. Therefore then the researcher developed the textbook in the composition of the PowerPoint, to support the bold reform steps in the installation. For this purpose, this research aims to learn how to develop a textbook “Ayo Belajar Bahasa Arab untuk MI Kelas IV” as well as to find out the effectiveness of the product from the development of this book. The approach adopted by the researcher in this research thesis is the methodology of scientific research and development (Research & Development R & D). The data collection consisted of direct observation, test, and questionnaire on the fourth-grade students. The Arabic book has been developed with the following steps: potential and issues, data collection, production design, certification production with the expert in teaching and learning, improvement of production, sampling of production in the sales group, and improvement of production. The use of books that have been developed with PowerPoint is effective in improving students understanding in learning Arabic.